Potential Future Engine Cycles for Improved Thermal Efficiency - Denny, Michael J. (My University, 2014)
A comparative 1-D analysis is undertaken between a baseline internal combustion engine (ICE) and several ICE operating cycle concepts which are intended to produce higher brake efficiencies than the baseline which runs on an Otto cycle. The baseline is a spark ignition gasoline engine representative of modern naturally aspirated automotive engines in its architecture and implemented technologies. Engine models are created and compared in the 1-D engine simulation software program GT-Power created by Gamma Technologies. After calibrating the performance of each model with the same resolution and tuning strategies, the result is that all of the concepts are less efficient than the baseline engine. Each engine concept requires additional hardware to separate the processes of the cycle within the engine. These components add to the mechanical friction, flow, and heat losses within the engine, and in some cases manage only to transfer exergy into different forms, not reduce it in a positive way. While the processes of these cycles are intended to improve the brake efficiency of an ICE through internal waste heat recovery or reduction, they first have to overcome the detrimental effects imposed by the architectures they require. This challenge proved too big to overcome and a net decrease in brake efficiency is realized.
Keywords: Farkostteknik; Hållbar utveckling; Energiteknik; Innovation och entreprenörskap (nyttiggörande); Transport; Vehicle Engineering; Sustainable Development; Energy Engineering; Innovation & Entrepreneurship; Transport